2013
DOI: 10.3389/fpubh.2013.00073
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Association between T. gondii Seropositivity and Obesity

Abstract: Obesity is a global public health problem that is linked with morbidity, mortality, and functional limitations and has limited options for sustained interventions. Novel targets for prevention and intervention require further research into the pathogenesis of obesity. Consistently, elevated markers of inflammation have been reported in association with obesity, but their causes and consequences are not well understood. An emerging field of research has investigated the association of infections and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 45 publications
4
36
1
3
Order By: Relevance
“…59 Therefore the elevated serum leptin observed in the infected mice may contribute to the lower frequencies of Treg and increased Th1 cells observed in the adipose tissue independently of the presence of parasites. Interestingly, a positive association between seropositivity for T. gondii and obesity has recently been reported 60 and plasma leptin levels were also increased in the serum of T. gondii-infected rats. 61 Our results add evidence in that apicomplexa parasites are able to affect metabolic parameters.…”
Section: Discussionmentioning
confidence: 92%
“…59 Therefore the elevated serum leptin observed in the infected mice may contribute to the lower frequencies of Treg and increased Th1 cells observed in the adipose tissue independently of the presence of parasites. Interestingly, a positive association between seropositivity for T. gondii and obesity has recently been reported 60 and plasma leptin levels were also increased in the serum of T. gondii-infected rats. 61 Our results add evidence in that apicomplexa parasites are able to affect metabolic parameters.…”
Section: Discussionmentioning
confidence: 92%
“…In humans, T. gondii infection has been associated with weight gain in pregnant women [42]. In addition, both T. gondii seroprevalence and high IgG anti- T. gondii antibody levels have been associated with obesity [43]. In fact, results of the positivity to both IgG antibodies against T. gondii and DNA of T. gondii in this study showed that women with obesity had a significantly higher prevalence of T. gondii than women without obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who were obese had a markedly higher T. gondii IgG titers compared to normal weight participants [652] . Also Baltaci and Mogulkoc [653] found that rats infected with T. gondii had significantly increased plasma leptin levels four weeks after the intraperitoneal injection of live parasites as compared with control animals ( Table 24).…”
Section: T Gondii Infectionmentioning
confidence: 91%
“…It was demonstrated that increased leptin levels correlated with enhanced concentrations of inflammatory markers in morbidly obese individuals [645] , and recently, Reeves et al [652] reported a significant positive association between T gondii seropositivity and obesity (p = 0.01). Individuals who were obese had a markedly higher T. gondii IgG titers compared to normal weight participants [652] .…”
Section: T Gondii Infectionmentioning
confidence: 97%